Environmental Carrying Capacity and Community-Based Governance of Mangrove Ecotourism in Tomini Bay - Anwar, Rustam; Abdurahman Kano Mohamad; Syaiful Umela; Romi Djafar (LPPM Politeknik Aceh Selatan, 2026)
Mangrove ecotourism is increasingly promoted as a pathway to reconcile conservation, livelihood diversification, and coastal resilience, yet destination growth often outpaces ecological thresholds, institutional capacity, and community readiness. Building on the literature review in the International Journals and incorporating recent studies compiled in Journals, this article presents an updated integrative review on the role of carrying capacity in sustainable mangrove ecotourism, with strategic implications for Tomini Bay, Indonesia. Using only the uploaded extraction sources, the review synthesizes advances in ecological suitability assessment, physical-real-effective carrying capacity, community participation, governance arrangements, social feasibility, and tourism management innovation across Indonesia and comparable settings. The synthesis shows that carrying capacity should not be treated merely as a visitor quota; it functions as a multidimensional governance instrument linking ecosystem integrity, visitor experience, local welfare, infrastructure limits, and enforcement capacity. Recent studies also reveal a persistent gap between technical suitability analysis and day-to-day management, especially in zoning, monitoring, promotion, digital visitor control, and benefit sharing. For Tomini Bay, the review proposes a conservation-first, community-based, and adaptive-capacity model that combines spatial zoning, phased visitor limits, ecosystem monitoring, participatory governance, and blue-economy livelihood integration. The article contributes a comparative evidence base, a strategic framework, and a research agenda for emerging mangrove destinations.